Advantages of G-band radar in multi-frequency liquid-phase microphysical retrievals - B. M. Courtier; A. Battaglia; K. Mroz; K. Mroz (Atmospheric Measurement Techniques)
Radar-based microphysical retrievals of cloud and droplet properties are vital for informing model parameterisations of clouds and precipitation, but these retrievals often do not capture the details of small droplets in light rain or drizzle. A state-of-the-art G-band radar is used here to demonstrate improvements to microphysical retrievals in a case study featuring light rain. Compared to W-band radar, improvements are seen in the retrieval of vertical wind speed due to the location of Mie minima at smaller droplet sizes with the G-band radar. This, in turn, has an impact on the retrieval of the drop size distribution, allowing for better accuracy in the retrieval of the characteristic drop diameter and for improvements in the retrieval of the particle number concentrations of small droplet sizes. The dual-Doppler velocity (DDV) between the Ka- and G-bands shows increased dynamic range compared to the Ka–W pairing, particularly for instances presenting small characteristic drop diameters. The increased attenuation experienced at G-band enables improved retrievals of liquid water content and precipitation rate when paired with W-band or Ka-band compared to the W-band and Ka-band pairing. This is particularly noticeable in periods of light rain when the W-band and Ka-band radars receive negligible attenuation, while the attenuation at G-band is much greater.